Sympathetic predominance before tourniquet deflation is associated with a reduction in arterial blood pressure after tourniquet deflation during total knee arthroplasty - Kim, E; Cho, M R; Byun, S H; A Lim, J; Chae, S; Choi, W K; Kim, I; Kim, J (Physiological research, 2021)
High dependency of arterial blood pressure (ABP) on enhanced sympathetic activity, which maintains vascular tone, leads to hypotension after hemodynamic insults that blunt the sympathetic activity. Therefore, we hypothesized that sympathovagal balance before tourniquet deflation (TD) determines the extent of a reduction in ABP after TD during total knee arthroplasty (TKA). Fifty-four hypertensive female patients undergoing TKA under spinal anesthesia were analyzed. The sympathovagal balance [low-to-high frequency ratio of heart rate variability (LF/HF)] before TD was defined as (LF/HF during 5 min before TD-preanesthetic LF/HF)/preanesthetic LF/HF (%). An increase in its value represents a shift in sympathovagal balance toward sympathetic predominance. The percent change in the mean ABP (MAP) after TD was defined as (minimum MAP during 10 min after TD-averaged MAP during 5 min before TD)/averaged MAP during 5 min before TD (%). Simple linear regression was performed to assess the correlation between the sympathovagal balance before TD and change in MAP after TD. The correlation was also assessed by multiple linear regression controlling for age, duration of tourniquet inflation, and spinal anesthesia-induced hypotension. Thirty-two minutes (on average) after tourniquet inflation, the MAP was decreased by 12.1 (-3.0 to 47.9) % [mean (range)] upon TD (P<0.001). The sympathovagal balance before TD was negatively proportional to the change in MAP after TD in both simple and multiple linear regression models (R2=0.323 and 0.340, P<0.001). A shift in sympathovagal balance toward sympathetic predominance before TD is associated with a decrease in ABP after TD.
Keywords: senioři; turnikety; Aging; Treatment Outcome; senioři nad 80 let; arteriální tlak; Hypertension; Anesthesia, Spinal; výsledek terapie; totální endoprotéza kolene; Middle Aged; spinální anestezie; Heart Rate; Arthroplasty, Replacement, Knee; srdeční frekvence; Aged, 80 and over; stárnutí; ženské pohlaví; Intraoperative Period; Humans; nervus vagus; lidé středního věku; hypertenze; sympatický nervový systém; Arterial Pressure; Sympathetic Nervous System; Vagus Nerve; peroperační doba; Female; Aged; Tourniquets; lidé